Gradient quenching hot stamping process for integrated automotive door rings

CN122913805APending Publication Date: 2026-10-16TIANJIN TAIZHENG MACHINERY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611336542.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-31
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

该方法存在以下缺陷:加热元件响应慢、温度控制精度低、模具结构复杂且易因热疲劳而损坏,同时加热区域与非加热区域之间存在明显的硬度突变界面,无法形成平滑的梯度过渡,影响零件的服役性能

Benefits of technology

1.本发明通过在合模保压阶段同时执行第一冷却路径和第二冷却路径,将工件划分为主体高强度区和软区区域,并分别以不同的冷却速率进行淬火,解决了现有技术无法在同一热冲压工序中同步获得全马氏体硬区与贝氏体-铁素体-马氏体梯度软区的技术问题。主体高强度区通过模具水路传导冷却,以不低于120℃/s的速率快速冷却,获得硬度380HV~550HV的全马氏体组织,保证碰撞传力路径的高强度需求;软区及梯度过渡区通过微型喷嘴动态喷射雾化介质,在工件表面形成动态汽膜,将冷却速率控制在30℃/s~80℃/s,获得硬度175HV~220HV的梯度混合组织,满足碰撞吸能区域的变形需求。本发明独创一模双冷的并行工艺,在不增加工序、不延长节拍的前提下,实现了同一工件内不同区域性能的按需定制,显著提升了门环的碰撞兼容性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122913805A_ABST
    Figure CN122913805A_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of hot stamping forming of automobile parts, and particularly relates to a gradient quenching hot stamping forming process method for an integrated automobile door ring. The present application is characterized in that a unique one-mold double-cooling parallel process is adopted, and the accurate gradient distribution of the hardness of different regions of the door ring workpiece is realized in the same hot stamping process without increasing the process and prolonging the beat, so that the defects of the prior art in the aspects of efficiency, precision, mold life and performance continuity are effectively overcome, and an efficient, controllable and high-quality industrial solution for the manufacturing of the integrated automobile door ring is provided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of hot stamping forming technology for automotive parts, and more particularly to a gradient quenching hot stamping forming process for integrated automotive door rings. Background Technology

[0002] With the increasing demands for lightweighting and collision safety in automobiles, hot stamping technology is widely used in the manufacturing of automotive body-in-white structural components. After hot stamping, the tensile strength of high-strength steels such as 22MnB5 can be increased from approximately 500MPa to approximately 1500MPa. Simultaneously, it simplifies the multiple forming processes required by traditional cold stamping into a single forming process, significantly reducing part weight and improving collision resistance.

[0003] In recent years, integrated door rings, as a cutting-edge product in the field of thermoforming, have integrated previously separate parts such as the A-pillar, B-pillar, door sill, and upper side beam into a single stamped part. This significantly reduces welding processes and the number of parts, improving overall vehicle rigidity and assembly efficiency. However, different areas of the integrated door ring perform drastically different functions during a collision: the upper A-pillar, the main body of the B-pillar, and the upper side beam need to withstand high loads to maintain the survival space of the passenger compartment, requiring extremely high strength; while the lower A-pillar and the waist of the B-pillar need to have a certain deformation energy absorption capacity to avoid rigid impact on the occupants, requiring lower hardness and good plasticity.

[0004] In existing technologies, the main methods for achieving hardness gradient distribution in different regions of the same part are as follows: 1. In-mold softening method: Heating elements (such as resistance heating rods) are embedded in specific areas of the mold cavity. During the quenching process, the areas requiring softening are locally heated to prevent martensitic transformation, thereby obtaining a soft region. This method has the following drawbacks: slow response of the heating elements, low temperature control accuracy, complex mold structure that is prone to damage due to thermal fatigue, and a significant hardness abrupt change interface between the heated and unheated areas, making it impossible to form a smooth gradient transition, which affects the service performance of the parts.

[0005] 2. Differential Thickness Plate or Welded Plate Method: This method involves welding materials of different thicknesses or grades into a single slab, utilizing the differences in hardenability or thickness of the materials to achieve hardness differences in different areas. This method is limited by material specifications and welding processes, resulting in a limited adjustable range for the hardness gradient, and the weld area may become a weak point in performance.

[0006] 3. Differentiated local cooling capacity design for molds: Different cooling rates are achieved by changing the density or flow rate of cooling channels in different areas of the mold cavity. This method is limited by the mold manufacturing process, resulting in a limited range and precision for adjusting the cooling capacity, making it difficult to achieve precise gradient control.

[0007] 4. Post-heating local tempering: This method involves locally induction tempering or laser tempering of fully martensitic parts after overall quenching to reduce local hardness. This method requires additional tempering equipment and processes, resulting in low production efficiency, high energy consumption, and significant difficulty in controlling the microstructure and properties of the tempered area.

[0008] In summary, the existing technology lacks a process method that can simultaneously, accurately, and controllably achieve gradient hardness distribution in different areas of the same door ring workpiece during hot stamping without increasing subsequent processes or sacrificing production efficiency. Summary of the Invention

[0009] The technical solution adopted by this invention to solve the above-mentioned technical problems is: a gradient quenching hot stamping forming process for integrated automotive door rings, comprising the following steps: Step S1: Provide a steel strip of 22MnB5 material, cut the steel strip into irregularly shaped pieces that match the contour of the door ring, perform laser welding on the irregularly shaped pieces to weld pieces of different thicknesses into an integral blank, and weld patch plates on the pre-set local reinforcement areas on the blank to obtain an integral door ring blank. The different thicknesses of the pieces are selected from 1.2mm, 1.4mm, 1.6mm, 1.8mm and 2.0mm. Step S2: The integrated door ring slab is fed into a continuous heating furnace and heated to 930℃±20℃ under a protective atmosphere. The temperature is then maintained so that the internal microstructure of the integrated door ring slab is completely transformed from ferrite and pearlite into homogeneous austenite. Step S3: Transfer the austenitized red-hot slab to the mold cavity of the hot forming press within 4 seconds after exiting the furnace. At this time, the surface temperature of the slab is not lower than 700°C. Then the press drives the mold to close the mold at a closing speed of 80mm / s to 200mm / s, and stamps the slab into the final shape of the door ring and keeps it in the closed state. Step S4: The mold is kept in the closed state, and the formed workpiece is subjected to zoned cooling to divide the workpiece into a main high-strength zone and a soft zone. The soft zone includes at least one soft zone and a gradient transition zone located between the soft zone and the main high-strength zone. Step S5: Open the mold and remove the formed door ring workpiece; Step S6: The removed door ring workpiece is trimmed and hole-processed by laser cutting to obtain the finished integrated automotive door ring; Step S7. For door ring workpieces made of bare plate, shot blasting is performed to remove surface oxide scale, and then the entire workpiece is sprayed with anti-rust oil; for door ring workpieces made of aluminum-silicon coated plate, the shot blasting step is skipped and the next inspection step is performed directly.

[0010] Furthermore, in step S1, the 22MnB5 material is either a 22MnB5 aluminum-silicon coated plate or a 22MnB5 bare plate; the laser welding involves butt welding a sheet with a thickness of 1.2mm to 1.4mm and a sheet with a thickness of 1.6mm to 2.0mm along the extension direction from the A-pillar to the B-pillar of the door ring; the patch plate has a thickness of 1.2mm to 2.0mm and is welded to the inner side of the B-pillar of the door ring or the hinge reinforcement area.

[0011] Furthermore, in step S2, the protective atmosphere is dry air or a mixture of nitrogen and natural gas, and the holding time of the slab at 930℃±20℃ is set to 1.2min~1.8min per millimeter of the maximum thickness of the slab, so that the austenitization of the entire cross section of the slab is uniform and no obvious oxidation and decarburization occurs on the surface.

[0012] Furthermore, in step S3, the transfer of the slab from the furnace to the start of mold closing is achieved by a robot clamping the edge of the slab. During the transfer, the slab is suspended and does not come into contact with cold metal. After mold closing, the contact pressure between the mold cavity and the door ring workpiece contact surface is not less than 15MPa, which is used to ensure the reliability of thermal contact for conduction cooling.

[0013] Furthermore, in step S4, the circulating liquid cooling medium used for cooling the high-strength zone of the main body is deionized water or ethylene glycol aqueous solution, the water inlet pressure of the mold water circuit is 0.8MPa~1.5MPa, the temperature rise of the cooling medium in the mold water circuit is controlled within ±2℃, and the heat flux at the contact surface between the mold cavity wall and the door ring workpiece is controlled at 3MW / m²~8MW / m².

[0014] Furthermore, in step S4, the projection positions of the soft zone and gradient transition zone on the door ring correspond to the areas that need to absorb energy during the side collision of the vehicle body, including the connecting transition section between the lower part of the A-pillar and the lower part of the B-pillar on the door ring, and the waist area of ​​the B-pillar. The main high-strength area corresponds to the upper part of the A-pillar, the main body of the B-pillar, and the upper side beam area on the door ring.

[0015] Furthermore, the main high-strength area in step S4 corresponds to the body force transmission path area on the door ring that needs to withstand the collision load. The first cooling path is implemented in this area: a circulating liquid cooling medium with a temperature controlled at 6℃~20℃ is continuously introduced into the cooling water channel inside the mold body. Through the direct contact conduction between the mold cavity wall and the surface of the door ring workpiece, the main high-strength area is rapidly cooled at a cooling rate of not less than 120℃ / s, and the microstructure is transformed into full martensite, with a hardness of 380HV~550HV. The soft zone and gradient transition zone correspond to the buffer area on the door ring that needs to absorb collision energy. A second cooling path is implemented for this area: multiple micro-nozzles are embedded in the mold cavity and located at the preset soft zone positions on the door ring workpiece to dynamically spray atomized liquid cooling medium onto the surface of the door ring workpiece at these positions. By independently adjusting the spray flow rate, atomization pressure, and spray sequence of each micro-nozzle, a dynamic vapor film with a thickness of 0.05 mm to 0.30 mm is formed locally on the surface of the door ring workpiece. The surface equivalent heat transfer coefficient of this local area is suppressed to 20% to 45% of the heat transfer coefficient of the main high-strength area. The cooling rate of the soft zone and gradient transition zone is controlled at 30℃ / s to 80℃ / s, and the microstructure is transformed into a gradient mixed structure containing bainite, ferrite, and martensite. The hardness is controlled at 175HV to 220HV. The mold closing and pressure holding state lasts for 6 to 15 seconds until the overall temperature of the door ring workpiece drops below 200°C.

[0016] Furthermore, the spray medium of the micro-nozzle is deionized water, the spray pressure is 0.3MPa~1.2MPa, the atomization cone angle is 30°~60°, the spray flow rate of each micro-nozzle is independently adjustable with an adjustment resolution of ±5mL / min, and the spray timing control accuracy is ±10ms; the dynamic vapor film is formed by the Leidenfrost effect triggered by atomized droplets on the red-hot surface of the door ring workpiece at 700℃~900℃, and the vapor film generates a heat insulation effect in the spray area, thereby reducing the local cooling rate.

[0017] Furthermore, a hardness transition zone with a width of 8mm to 25mm is defined between the soft area and the gradient transition zone and the adjacent high-strength area of ​​the main body. Along the direction of the hardness transition zone from the high-strength area side of the main body to the soft area side, the spray flow rate of the micro-nozzle gradually increases, so that the surface hardness of the door ring workpiece continuously decreases from 380HV to 550HV to 175HV to 220HV, forming a continuous gradient hardness distribution without abrupt interface changes.

[0018] Furthermore, the next-order check in step S7 includes the following steps: Step S71: Use a coordinate measuring machine or blue light scanner to check the dimensions and geometric tolerances of the laser-cut door ring workpiece to confirm that its contour, hole position and trimming line meet the requirements of the drawing. Step S72: At the preset soft area, gradient transition area and main body high strength area positions on the door ring workpiece, use a portable hardness tester to perform hardness sampling test to verify that the hardness of the soft area is 175HV~220HV, the hardness of the main body high strength area is 380HV~550HV, and the hardness of the gradient transition area changes continuously. Step S73: Visually inspect the surface of the door ring workpiece to confirm that there are no scratches, indentations, peeling of the plating, cracks or oxidation spots. Step S74: Verify the laser QR code or steel stamp mark on the door ring workpiece to ensure that the batch number, part number and production date information are clearly readable and consistent with the production record.

[0019] The advantages of this invention are: 1. This invention solves the technical problem of existing technologies being unable to simultaneously obtain a fully martensitic hard zone and a bainite-ferrite-martensitic gradient soft zone in the same hot stamping process by simultaneously executing a first cooling path and a second cooling path during the mold closing and pressure holding stage. The main high-strength zone is rapidly cooled at a rate of no less than 120℃ / s through mold water conduction cooling to obtain a fully martensitic structure with a hardness of 380HV to 550HV, ensuring the high strength requirements of the impact force transmission path. The soft zone and gradient transition zone are dynamically sprayed with atomized medium through micro-nozzles to form a dynamic vapor film on the workpiece surface, controlling the cooling rate at 30℃ / s to 80℃ / s to obtain a gradient mixed structure with a hardness of 175HV to 220HV, meeting the deformation requirements of the impact energy absorption zone. This invention features a unique parallel process of dual cooling in a single mold, achieving on-demand customization of the performance of different regions within the same workpiece without increasing the number of processes or extending the cycle time, significantly improving the impact compatibility of the door ring.

[0020] 2. This invention solves the technical problems of rough temperature control and easy mold damage in traditional in-mold heating and softening methods by using micro-nozzles to dynamically spray atomized liquid cooling medium and forming a dynamic vapor film with controllable thickness on the red-hot surface of the workpiece using the Leidenfrost effect. The spray pressure, flow rate, and timing of the atomized droplets can be independently and precisely adjusted, and the vapor film thickness can be controlled within the range of 0.05mm to 0.30mm, thereby precisely suppressing the surface equivalent heat transfer coefficient of the soft area to 20% to 45% of the heat transfer coefficient of the main area. Compared with electric heating elements, this solution has a fast response speed (millisecond level), high control accuracy (flow rate resolution ±5mL / min, timing accuracy ±10ms), does not increase the thermal load on the mold, has a longer mold life, and lower maintenance costs.

[0021] 3. This invention solves the technical problem of stress concentration and service performance degradation caused by abrupt hardness transitions between the soft zone and the high-strength zone of the main body. This is achieved by setting a hardness transition zone with a width of 8mm to 25mm between the soft zone and the main body, and gradually increasing the jet flow rate of the micro-nozzle along the transition zone in a linear or exponential manner. This results in a continuous decrease in workpiece surface hardness from 380HV to 550HV to 175HV to 220HV. This continuous gradient hardness distribution without abrupt transitions allows the door ring to smoothly transfer loads during collisions, avoiding tearing or fracture at the interface between the hard and soft zones, and significantly improving the overall structural integrity and energy absorption efficiency of the part.

[0022] 4. This invention solves the technical problem of matching the collision functional requirements and material properties of different areas of the door ring by placing the soft zone and gradient transition zone in the transition section connecting the lower A-pillar and lower B-pillar of the door ring and in the waist area of ​​the B-pillar, and placing the main high-strength zone in the upper A-pillar, the main body of the B-pillar, and the upper side beam area. This layout fully utilizes the integrated advantages of the hot-stamped door ring, placing the high-strength zone in the skeletal frame of the occupant compartment and the soft zone in the collision energy absorption buffer zone, achieving a collision energy management that combines rigidity and flexibility, and taking into account both maintaining the occupant survival space and controlling the collision acceleration.

[0023] 5. This invention solves the complete manufacturing chain problem of complex integrated door rings by combining laser welding, patch plate welding, and gradient quenching processes, and by setting separate post-processing steps for different materials (bare plate / aluminum-silicon coated plate). The welded plate achieves material matching of different thicknesses, the patch plate achieves local thickening and reinforcement, and the gradient quenching achieves performance zoning. The three work together to form a complete solution from blank to finished product. At the same time, the aluminum-silicon coated plate skips the shot blasting step and directly proceeds to the next inspection, simplifying the process and reducing production costs.

[0024] In summary, this invention achieves a precise gradient distribution of hardness in different areas of the door ring workpiece in the same hot stamping process, effectively overcoming the shortcomings of existing technologies in terms of efficiency, precision, mold life, and performance continuity, and providing an efficient, controllable, and high-quality industrial solution for the manufacturing of integrated automotive door rings. Attached Figure Description

[0025] To more clearly illustrate the specific embodiments of the present invention or the technical solutions in the prior art, the drawings used in the description of the specific embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For those skilled in the art, other drawings can be obtained from these drawings without creative effort.

[0026] Figure 1 The flowchart illustrates the gradient quenching hot stamping forming process for an integrated automotive door ring provided by this invention.

[0027] Figure 2 This is a product image of an integrated automotive door ring manufactured using the process method of this invention. Detailed Implementation

[0028] The technical solution of the present invention will now be clearly and completely described with reference to the accompanying drawings. Obviously, the described embodiments are only some, not all, of the embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0029] Figure 1 The flowchart illustrates the gradient quenching hot stamping forming process for an integrated automotive door ring provided by this invention. Figure 2 The image shows an integrated automotive door ring manufactured using the process method of this invention. Figure 1 As shown, this invention provides a gradient quenching hot stamping forming process for an integrated automotive door ring. This method aims to solve the technical problem mentioned in the background art, where existing technologies cannot simultaneously obtain a fully martensitic hard region and a bainite-ferrite-martensitic gradient soft region in the same hot stamping process. This invention achieves a precise gradient distribution of hardness in different regions of the door ring through an innovative dual-cold partitioning cooling strategy, thereby balancing the high strength requirements of the impact force transmission path with the deformation capacity of the energy-absorbing region.

[0030] The present invention will be described in detail below with reference to specific embodiments. For ease of understanding, this embodiment takes the integrated left front door ring of a certain vehicle model as an example. The door ring includes areas such as the A-pillar, B-pillar, door sill, and upper beam. The blank is verified using two materials: 22MnB5 aluminum-silicon coated plate and bare plate.

[0031] Example 1: Step S1. In this example, 22MnB5 aluminum-silicon coated steel sheets with thicknesses of 1.2mm, 1.4mm, 1.6mm, 1.8mm, and 2.0mm were selected. The aluminum-silicon coating composition, by mass percentage, was Al 88%, Si 10%, and Fe 2%, with a double-sided coating weight of approximately 150g / m². After uncoiling and leveling, the steel strip was blanked according to the outline of the door ring using a CNC laser blanking line to obtain multiple irregularly shaped sheets. Strict control of the outline accuracy was maintained during blanking, with edge burr height not exceeding 0.1mm.

[0032] The irregularly shaped sheets obtained from the above blanking process are then laser-welded according to design requirements. The specific steps are as follows: The upper part of the A-pillar (1.6mm thick) and the lower part of the A-pillar (1.4mm thick) are butt-welded together, with the weld extending along the axis of the A-pillar.

[0033] The main body of the B-pillar (1.8mm thick) is butt-welded to the upper part of the A-pillar (1.6mm thick) and the rear part of the A-pillar (1.6mm thick), with the weld direction consistent with the axis of the B-pillar.

[0034] The middle section of the sill area (1.2mm thick) is welded to the lower part of the A-pillar (1.4mm) and the lower part of the B-pillar (1.8mm thick), respectively, and the tail of the sill (1.2mm) is welded to the lower part of the B-pillar (1.8mm).

[0035] The welding was performed using an IPG YLS-6000 fiber laser welding system with the following parameters: laser power 4.5kW, welding speed 4.0m / min, focal point at the center of the plate thickness, and shielding gas 99.999% high-purity argon at a flow rate of 20L / min. After welding, the weld underwent 100% visual inspection and ultrasonic testing to ensure the absence of defects such as porosity, cracks, and lack of fusion, and that the tensile strength of the weld was not less than 90% of the base metal.

[0036] Patches were welded to the inside of the B-pillar of the door ring (corresponding to the seatbelt anchorage area) and the hinge reinforcement area (where the upper end of the A-pillar connects to the door hinge). The patch panels were made of 22MnB5 aluminum-silicon coated steel, with a thickness of 2.0mm. Resistance spot welding was used, with a weld spacing ≥20mm and a weld nugget diameter ≥5mm. A peel test was performed after welding to confirm the weld strength was up to standard.

[0037] At this point, a complete integrated door ring blank is obtained, with an overall outline size of approximately 2080mm in length and 1400mm in width, and a blank weight of approximately 17.50kg.

[0038] Step S2: The integrated door ring slab obtained in step S1 is fed into a continuous roller hearth furnace (furnace length 36m, 13 heating zones in total). Dry air is introduced into the furnace, and the dew point is controlled below -20℃ to prevent hydrogen embrittlement of the slab.

[0039] The temperature zones of the heating furnace are set as follows: preheating zone (zones 1-2) 850-880℃, heating zone (zones 3-9) 890-920℃, and soaking zone (zones 10-13) 930℃±10℃. The slab running speed in the furnace is set at 1.5 minutes per millimeter based on the maximum slab thickness (2.0mm), with a total heating time of approximately 3 minutes (2.0mm × 1.5min / mm = 3.0min), ensuring that the entire cross-section of the slab reaches the austenitizing temperature. Thermocouples inside the furnace monitor the slab temperature in real time. When the center temperature of the slab reaches 920℃~940℃, timing and holding begin, with a holding time of no less than 2.5 minutes.

[0040] Tests showed that the surface temperature of the slab when it came out of the furnace was 930℃ (infrared thermometer, emissivity set to 0.85). The internal microstructure of the slab had completely transformed from the original ferrite + pearlite to homogeneous austenite, and the carbides were fully dissolved.

[0041] Step S3: Immediately after the slab exits the furnace, a three-axis robotic arm clamps the edge of the slab using an end effector (the clamping point is located in the non-functional area around the slab), and transfers the red-hot slab to the mold cavity of the hot forming press with maximum acceleration. The transfer path is optimized through simulation, and the total transfer time is controlled within 3.2 seconds (less than 4 seconds). During the transfer, the slab is suspended and does not come into contact with any cold metal to avoid excessive heat loss. When the slab enters the mold cavity, the surface temperature of the slab, measured by the infrared temperature measuring array installed at the mold entrance, is still 765℃ (not lower than 700℃). The press slide descends rapidly at a closing speed of 120mm / s (within the range of 80~200mm / s), and the mold closes. During the mold closing process, the slab is stretched, bent, and flanged within the mold cavity, ultimately conforming to the mold surface to form a door ring shape. After mold closing, the mold locking force is maintained at 25000kN, ensuring that the contact pressure between the mold cavity wall and the workpiece surface reaches 18MPa (not less than 15MPa), thus guaranteeing the reliability of thermal contact for subsequent conduction cooling. The entire stamping stroke, from the blank entering the mold to the completion of mold closing, takes approximately 0.8 seconds.

[0042] Step S4: Keep the mold in the closed state and simultaneously start the zoned cooling system. Based on the door ring collision function requirements, divide the workpiece into the following cooling zones: High-strength main body area: This area corresponds to the A-pillar, B-pillar (upper and middle parts of the B-pillar), lower A-pillar, sill body, and other vehicle body force transmission paths that need to withstand collision loads. This area requires a final hardness of 380HV to 550HV and a microstructure of full martensite.

[0043] Soft zone: This includes a soft zone and a gradient transition zone located between the soft zone and the main high-strength zone. The soft zone corresponds to the connecting transition section at the bottom of the B-pillar, requiring a hardness of 175HV to 220HV, and a microstructure of a gradient mixture of bainite, ferrite, and martensite. The gradient transition zone is located between the soft zone and the main high-strength zone, with a width of 15mm (within the range of 8 to 25mm), and requires a continuous decrease in hardness from the main zone side to the soft zone side.

[0044] For the high-strength areas of the main body, conduction cooling is achieved through internal cooling water channels within the mold body. The mold material is HTCS-130 hot work die steel. Conformal cooling water channels are machined on the back of the mold cavity (10mm from the cavity surface), with a channel diameter of φ10mm and a channel spacing of 12mm. The cooling medium is deionized water (conductivity ≤10μS / cm), supplied by a chiller unit. The inlet water temperature is controlled at 10℃±1℃ (within the range of 6~20℃), and the inlet water pressure is 1.2MPa (within the range of 0.8~1.5MPa). The cooling water flows turbulently in the mold water channels (Reynolds number Re>4000) at a flow rate of approximately 80L / min. The temperature rise of the cooling medium in the mold water channels is maintained within ±1.5℃ (less than ±2℃) by a PID controller.

[0045] During the mold closing and pressure holding process, the mold cavity wall is in close contact with the workpiece surface. Heat is transferred to the mold through contact conduction and then carried away by the cooling water inside the mold. Actual measurements using a heat flow sensor show that the heat flux at the contact surface between the mold cavity wall and the workpiece is approximately 5.5 MW / m² (within the range of 3–8 MW / m²). The workpiece in this area cools rapidly at a rate of approximately 150°C / s (not less than 120°C / s), resulting in a diffusionless phase transformation of the microstructure, with austenite transforming into full martensite. At the end of the pressure holding process, the hardness of this area is measured at 460 HV (within the range of 380–550 HV).

[0046] For the soft zone and gradient transition zone, dynamic atomization cooling is achieved using micro-nozzles pre-embedded within the mold cavity. The micro-nozzles are arranged as follows: On the mold cavity surface corresponding to the soft zone (lower part of the B-pillar), micro-nozzles are arranged in a matrix, with a nozzle spacing of 25mm, for a total of 36 nozzles. On the mold cavity surface corresponding to the gradient transition zone (a 15mm wide strip), a row of micro-nozzles is arranged along the transition zone direction with a denser spacing (10mm), for a total of 12 nozzles. The micro-nozzles are precision-machined stainless steel atomizing nozzles, and the spray medium is deionized water (sharing a water supply system with the first cooling path, but controlled by an independent booster pump and pressure regulating valve). The spray parameters are as follows: Spray pressure: 0.6MPa for the soft zone, linearly increasing from 0.3MPa on the main body side to 0.8MPa on the soft zone side in the gradient transition zone (both within the range of 0.3~1.2MPa). Atomization cone angle: 45° (within the range of 30°~60°). The average droplet diameter is approximately 50μm. Injection flow rate: The flow rate of each nozzle in the soft zone is 80 mL / min, and the flow rate of each nozzle in the gradient transition zone increases linearly from 30 mL / min on the main zone side to 120 mL / min on the soft zone side, with a flow rate adjustment resolution of ±5 mL / min. Injection timing: Injection begins 0.5 seconds after mold closing and continues until 1 second before the end of pressure holding, with a timing control accuracy of ±10 ms.

[0047] When atomized droplets come into contact with the surface of a red-hot workpiece at 700℃~900℃, the Leidenfrost effect is triggered, and the droplets form a stable vapor film (dynamic vapor film) on the workpiece surface. This vapor film separates the droplets from the workpiece surface, significantly reducing heat transfer efficiency. Measurements taken using a high-speed camera and a heat flux sensor show that the thickness of this dynamic vapor film is approximately 0.15mm (within the range of 0.05~0.30mm), which suppresses the surface equivalent heat transfer coefficient in the soft zone and gradient transition zone to 30% of the heat transfer coefficient in the main high-intensity zone (within the range of 20%~45%). Therefore, the cooling rate in this region was controlled at about 55℃ / s (in the range of 30 to 80℃ / s), avoiding the critical cooling rate for martensitic transformation (about 27℃ / s). This allowed austenite to partially transform into bainite (about 40% by volume) and ferrite (about 25%) during the cooling process, while the remaining austenite (about 35%) transformed into martensite during continued cooling, ultimately forming a gradient mixed structure of bainite-ferrite-martensite.

[0048] At the end of the pressure holding period, the hardness of the soft zone was 195 HV (within the range of 175–220 HV). The hardness of the gradient transition zone decreased continuously from 450 HV on the main body side to 200 HV on the soft zone side. Measurements were taken every 2 mm along the transition zone using a microhardness tester, showing a linear decrease in hardness. The entire mold-closing pressure holding period lasted 8 seconds (within the range of 6–15 seconds). During this period, the overall temperature of the workpiece continued to decrease. At the end of the pressure holding period, the temperature of the thickest part of the workpiece (B-pillar main body, 2.0 mm), measured by thermocouples embedded in the non-functional area of ​​the workpiece, had dropped to 185℃, and the temperature of the thinnest part (threshold, 1.2 mm) had dropped to 120℃, both below 200℃. The quenching process was thus completed.

[0049] Step S5: Stop the atomizing medium spraying from the micro-nozzle, the press slide returns, and the mold opens. The formed door ring workpiece is removed from the mold cavity by the robotic arm end effector and placed on the cooling conveyor belt. The workpiece surface temperature is approximately 150°C; allow it to cool naturally to room temperature.

[0050] Step S6: Transfer the cooled door ring workpiece to the laser cutting station. Use a Trumpf TruLaser Cell 8030 3D five-axis laser cutting machine to trim and machine holes in the workpiece. Cutting parameters: laser power 4kW, cutting speed 8m / min, auxiliary gas is compressed air (pressure 0.8MPa). Cutting includes: trimming along the outer circumference of the door ring, removing additional process surfaces. Cutting the hinge mounting holes (φ12mm, 4 holes) at the upper end of the A-pillar. Cutting the seat belt anchoring holes (φ15mm, 1 hole) and buckle mounting holes (φ10mm, 2 holes) in the B-pillar, and cutting the wiring harness through holes (φ20mm, 2 holes) in the sill area. Cutting the positioning holes (φ8mm, 4 holes) on the upper beam. After cutting, the hole positions are inspected; the positional tolerance is ±0.3mm, and the contour tolerance is ±0.5mm, both conforming to the drawing requirements.

[0051] Step S7: In this embodiment, a 22MnB5 aluminum-silicon coated plate is used, therefore the shot blasting step is skipped, and the process proceeds directly to the next inspection step. The next inspection step includes the following steps: using a Zeiss CONTURA G2 coordinate measuring machine, a full-dimensional inspection of the door ring workpiece is performed. A total of 120 inspection points are used, covering key sections such as the A-pillar, B-pillar, sill, and upper beam. Inspection results: the deviation of all measuring points is within ±0.5mm, the contour is 0.6mm, and the maximum hole position deviation is 0.25mm, which meets the drawing requirements.

[0052] Hardness testing (Vickers hardness, 10kg load) was performed at the following locations on the door ring workpiece: Upper A-pillar (high-strength main body area): 460HV, 455HV, 465HV, with an average value of 460HV.

[0053] B-pillar main body (high strength zone): 445HV, 440HV, 450HV, average value 445HV.

[0054] Lower part of B-pillar (soft area): 195HV, 190HV, 200HV, average value 195HV.

[0055] Gradient transition zone: A point was measured every 2 mm along the transition zone. The hardness values ​​were 450HV, 420HV, 390HV, 355HV, 320HV, 285HV, 250HV, 215HV, and 200HV, showing a continuous decrease without abrupt changes.

[0056] Metallographic samples were taken from the soft region at the bottom of column B. After mounting, grinding, and polishing, the samples were etched with 4% nitric acid alcohol and observed under an optical microscope. The microstructure consisted of bainite (dark needle-like) + ferrite (white blocky) + martensite (bright lath-like), with volume fractions of approximately 40%, 25%, and 35%, respectively. The grain size was ASTM No. 9. Metallographic samples were taken from the top of column A. The microstructure was entirely martensite (lath martensite + a small amount of retained austenite), with a martensite volume fraction ≥97%.

[0057] The workpiece surface is visually inspected on a dedicated lighting inspection table to confirm the absence of defects such as scratches, indentations, coating peeling, cracks, and oxidation spots. The aluminum-silicon coating surface is a uniform silver-gray color with no exposed iron.

[0058] Verify the laser QR code on the workpiece (marked simultaneously by the laser cutting machine), scan and read the batch number, part number, and production date information, and ensure it matches the records in the MES system.

[0059] After all inspection items pass, the workpiece enters the packaging and shipping stage.

[0060] Example 2: This example is basically the same as Example 1, except that the slab material is 22MnB5 bare board (without aluminum-silicon coating), and the post-processing steps are different. Only the differences are described below.

[0061] Step S1: Use 22MnB5 bare board (acid-pickled surface), with the same thickness specifications and welding scheme as in Example 1. Since bare boards are easily oxidized during heating, the protective atmosphere requirements in the heating furnace are higher: nitrogen gas fraction ≥ 97%, natural gas volume fraction ≤ 3%. The patch board welding process remains unchanged.

[0062] Step S2, the heating parameters for austenitization, are the same as in Example 1. Since the bare plate has no protective coating, the surface of the slab remains silver-gray after exiting the furnace, with no obvious oxide scale.

[0063] Steps S3-S6, transfer, stamping, quenching, and laser cutting are exactly the same as steps S3-S6 in Example 1. The zoned cooling parameters, mold structure, and nozzle arrangement are also the same. After quenching, the hardness of the high-strength zone of the main body is 450 HV, the hardness of the soft zone is 200 HV, the gradient transition zone width is 15 mm, and the hardness continuously decreases.

[0064] Step S7: Since a thin oxide scale (approximately 2-5 μm thick) will form on the surface of the bare plate during hot stamping, shot blasting is required to remove the oxide scale and improve the surface quality.

[0065] Step S71: Use a tracked shot blasting machine with cast steel shot as the blasting medium. The blasting time is 5 minutes, and the blasting speed is 60 m / s. After shot blasting, the workpiece surface has a uniform silvery-white metallic luster, and the surface roughness Ra ≤ 3.2 μm.

[0066] Step S71: Immediately after shot blasting, perform rust prevention treatment by electrostatically spraying the entire workpiece with rust-preventive oil (Rustillo DW 385) to a thickness of 5–10 μm. After spraying, allow the workpiece to stand in the air for 30 minutes to allow the solvent to evaporate and form a dry film.

[0067] Step S73: The inspection process is the same as in Example 1 (dimensions, hardness, metallography, appearance, markings). Since the bare plate has no coating, special attention should be paid to the absence of rust and surface damage caused by excessive shot blasting during the visual inspection. After passing the inspection, the plate is put into storage.

[0068] Taking the right front door ring of a certain SUV model as an example, the sheet thickness combination is as follows: upper A-pillar 1.6mm, lower A-pillar 1.4mm, B-pillar body 1.8mm, door sill 1.2mm, upper side beam 1.6mm. The patch plate is 2.0mm thick and welded to the inside of the B-pillar.

[0069] The gradient transition zone width was set to 20 mm (within the range of 8–25 mm), and the flow rate of the micro-nozzle along the transition zone increased linearly from 20 mL / min on the main body side to 100 mL / min on the soft area side. Other process parameters were the same as in Example 1. The final test results showed a hardness of 435 HV in the high-strength zone of the main body, 185 HV in the soft area, and a transition zone hardness that continuously decreased from 430 HV to 180 HV, with a near-linear decrease curve and no abrupt changes. The metallographic structure was consistent with that of Example 1.

[0070] To verify the rationality of the process parameters of this invention, multiple sets of comparative experiments were conducted. The results showed that when the micro-nozzle injection pressure was below 0.3 MPa, the atomization effect was insufficient, the vapor film was unstable, and the cooling rate was too high (>100℃ / s), resulting in the soft area hardness exceeding 250 HV, failing to meet the energy absorption requirements. When the injection pressure was above 1.2 MPa, the droplets penetrated the vapor film and directly contacted the workpiece, causing a sharp increase in the cooling rate, similarly leading to excessive hardness in the soft area. Therefore, a pressure range of 0.3–1.2 MPa is crucial for ensuring the stable existence of the vapor film and achieving weak cooling. When the vapor film thickness was within the range of 0.05–0.30 mm, the cooling rate of the soft area could be stably controlled at 30–80℃ / s, and the hardness fell within the target range of 175–220 HV. A vapor film that was too thin (<0.05 mm) resulted in insufficient heat insulation and excessively rapid cooling; a vapor film that was too thick (>0.30 mm) resulted in excessively slow cooling, potentially leading to excessive ferrite in the soft area and low hardness (<150 HV). In this invention, a transition band width of 8–25 mm enables a continuous gradient change in hardness. When the width is less than 8 mm, the hardness change is too steep, approaching an abrupt interface, which is detrimental to stress transfer. When the width is greater than 25 mm, the transition band occupies too much of the effective area of ​​the gate ring, weakening the area of ​​the main high-strength zone and affecting overall impact performance. A mold closing and holding pressure time of 6–15 seconds is sufficient to reduce the overall workpiece temperature to below 200°C, ensuring complete martensitic transformation. If the holding pressure time is less than 6 seconds, the workpiece center temperature remains above the martensitic termination temperature (Msf), potentially leading to excessive retained austenite and low hardness. A holding pressure time exceeding 15 seconds is detrimental to production efficiency and may over-cool the mold, affecting the heating efficiency of the next cycle.

[0071] The above embodiments detail the specific implementation of the gradient quenching hot stamping forming process method for integrated automotive door rings according to the present invention. Through the complete process of steps S1 to S7, especially the dual-path parallel quenching method in step S4, which combines mold water conduction cooling with dynamic atomization jetting of micro-nozzles for weak cooling, the present invention achieves synchronous, precise, and controllable forming of the main high-strength zone (full martensite, hardness 380–550 HV) and the soft zone and gradient transition zone (bainite-ferrite-martensite gradient mixed structure, hardness 175–220 HV) within the same door ring workpiece. This method does not add extra processes, does not extend the production cycle, has a reliable mold structure, and high control precision, meeting the needs of mass industrial production.

[0072] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A gradient quenching hot stamping forming process for integrated automotive door rings, characterized in that, Includes the following steps: Step S1: Provide a steel strip of 22MnB5 material, cut the steel strip into irregularly shaped pieces that match the contour of the door ring, perform laser welding on the irregularly shaped pieces to weld pieces of different thicknesses into an integral blank, and weld patch plates on the pre-set local reinforcement areas on the blank to obtain an integral door ring blank. The different thicknesses of the pieces are selected from 1.2mm, 1.4mm, 1.6mm, 1.8mm and 2.0mm. Step S2: The integrated door ring slab is fed into a continuous heating furnace and heated to 930℃±20℃ under a protective atmosphere. The temperature is then maintained so that the internal microstructure of the integrated door ring slab is completely transformed from ferrite and pearlite into homogeneous austenite. Step S3: Transfer the austenitized red-hot slab to the mold cavity of the hot forming press within 4 seconds after exiting the furnace. At this time, the surface temperature of the slab is not lower than 700°C. Then the press drives the mold to close the mold at a closing speed of 80mm / s to 200mm / s, and stamps the slab into the final shape of the door ring and keeps it in the closed state. Step S4: The mold is kept in the closed state, and the formed workpiece is subjected to zoned cooling to divide the workpiece into a main high-strength zone and a soft zone. The soft zone includes at least one soft zone and a gradient transition zone located between the soft zone and the main high-strength zone. Step S5: Open the mold and remove the formed door ring workpiece; Step S6: The removed door ring workpiece is trimmed and hole-processed by laser cutting to obtain the finished integrated automotive door ring; Step S7: For door ring workpieces made of bare plate, shot blasting is performed to remove surface oxide scale, and then the entire workpiece is sprayed with anti-rust oil; for door ring workpieces made of aluminum-silicon coated plate, the shot blasting step is skipped and the next inspection step is performed directly.

2. The gradient quenching hot stamping forming process for an integrated automotive door ring according to claim 1, characterized in that, In step S1, the 22MnB5 material is either a 22MnB5 aluminum-silicon coated plate or a 22MnB5 bare plate; the laser welding involves butt welding a sheet with a thickness of 1.2mm to 1.4mm and a sheet with a thickness of 1.6mm to 2.0mm along the extension direction from the A-pillar to the B-pillar of the door ring; the patch plate has a thickness of 1.2mm to 2.0mm and is welded to the inner side of the B-pillar of the door ring or the hinge reinforcement area.

3. The gradient quenching hot stamping forming process for an integrated automotive door ring according to claim 1, characterized in that, In step S2, the protective atmosphere is dry air or a mixture of nitrogen and natural gas. The holding time of the slab at 930℃±20℃ is set to 1.2min~1.8min per millimeter of the maximum thickness of the slab, so that the austenitization of the entire cross section of the slab is uniform and no obvious oxidation and decarburization occurs on the surface.

4. The gradient quenching hot stamping forming process for an integrated automotive door ring according to claim 1, characterized in that, In step S3, the transfer of the slab from the furnace to the start of mold closing is achieved by a robot clamping the edge of the slab. During the transfer, the slab is suspended and does not come into contact with cold metal. After mold closing, the contact pressure between the mold cavity and the door ring workpiece contact surface is not less than 15MPa, which is used to ensure the reliability of thermal contact for conduction cooling.

5. The gradient quenching hot stamping forming process for an integrated automotive door ring according to claim 1, characterized in that, In step S4, the circulating liquid cooling medium used for cooling the high-strength zone of the main body is deionized water or ethylene glycol aqueous solution. The water inlet pressure of the mold water circuit is 0.8MPa to 1.5MPa. The temperature rise of the cooling medium in the mold water circuit is controlled within ±2℃. The heat flux at the contact surface between the mold cavity wall and the door ring workpiece is controlled between 3MW / m² and 8MW / m².

6. The gradient quenching hot stamping forming process for an integrated automotive door ring according to claim 1, characterized in that, In step S4, the projection positions of the soft zone and gradient transition zone on the door ring correspond to the areas that need to absorb energy during the side collision of the vehicle body, including the connecting transition section between the lower part of the A-pillar and the lower part of the B-pillar on the door ring, and the waist area of ​​the B-pillar. The main high-strength area corresponds to the upper part of the A-pillar, the main body of the B-pillar, and the upper side beam area on the door ring.

7. The gradient quenching hot stamping forming process for an integrated automotive door ring according to claim 1, characterized in that, The main high-strength area in step S4 corresponds to the body force transmission path area on the door ring that needs to withstand the collision load. The first cooling path is implemented in this area: a circulating liquid cooling medium with a temperature controlled at 6℃~20℃ is continuously introduced into the cooling water channel inside the mold body. Through the direct contact conduction between the mold cavity wall and the surface of the door ring workpiece, the main high-strength area is rapidly cooled at a cooling rate of not less than 120℃ / s, and the microstructure is transformed into full martensite, with a hardness of 380HV~550HV. The soft zone and gradient transition zone correspond to the buffer area on the door ring that needs to absorb collision energy. A second cooling path is implemented for this area: multiple micro-nozzles are embedded in the mold cavity and located at the preset soft zone positions on the door ring workpiece to dynamically spray atomized liquid cooling medium onto the surface of the door ring workpiece at these positions. By independently adjusting the spray flow rate, spray pressure, and spray sequence of each micro-nozzle, a vapor film with a thickness of 0.05 mm to 0.30 mm is formed locally on the surface of the door ring workpiece. The surface equivalent heat transfer coefficient of this local area is suppressed to 20% to 45% of the heat transfer coefficient of the main high-strength area. The cooling rate of the soft zone and gradient transition zone is controlled at 30℃ / s to 80℃ / s, and the microstructure is transformed into a gradient mixed structure containing bainite, ferrite, and martensite. The hardness is controlled at 175HV to 220HV. The mold closing and pressure holding state lasts for 6 to 15 seconds until the overall temperature of the door ring workpiece drops below 200°C.

8. The gradient quenching hot stamping forming process for an integrated automotive door ring according to claim 7, characterized in that, The micro-nozzle uses deionized water as the injection medium, with an injection pressure of 0.3MPa to 1.2MPa and an atomization cone angle of 30° to 60°. The injection flow rate of each micro-nozzle is independently adjustable with an adjustment resolution of ±5mL / min, and the injection timing control accuracy is ±10ms. The dynamic vapor film is formed by the Leidenfrost effect triggered by atomized droplets on the red-hot surface of the door ring workpiece at 700°C to 900°C. This vapor film generates a heat insulation effect in the injection area, reducing the local cooling rate.

9. The gradient quenching hot stamping forming process for an integrated automotive door ring according to claim 7, characterized in that, A hardness transition zone with a width of 8mm to 25mm is defined between the soft area and the gradient transition zone and the adjacent high-strength area of ​​the main body. Along the hardness transition zone from the high-strength area side of the main body to the soft area side, the jet flow rate of the micro-nozzle gradually increases, so that the surface hardness of the door ring workpiece continuously decreases from 380HV to 550HV to 175HV to 220HV, forming a continuous gradient hardness distribution without abrupt interface changes.

10. The gradient quenching hot stamping forming process for an integrated automotive door ring according to claim 1, characterized in that, The next step in step S7 includes the following steps: Step S71: Use a coordinate measuring machine or blue light scanner to check the dimensions and geometric tolerances of the laser-cut door ring workpiece to confirm that its contour, hole position and trimming line meet the requirements of the drawing. Step S72: At the preset soft area, gradient transition area and main body high strength area positions on the door ring workpiece, use a portable hardness tester to perform hardness sampling test to verify that the hardness of the soft area is 175HV~220HV, the hardness of the main body high strength area is 380HV~550HV, and the hardness of the gradient transition area changes continuously. Step S73: Visually inspect the surface of the door ring workpiece to confirm that there are no scratches, indentations, peeling of the plating, cracks or oxidation spots. Step S74: Verify the laser QR code or steel stamp mark on the door ring workpiece to ensure that the batch number, part number and production date information are clearly readable and consistent with the production record.